Gay men's identity work and the social construction of discrimination. Issue 1 (3rd April 2017) - Greenland, Katy; Taulke-Johnson, Richard
ABSTRACT: Although the lives of gay men in the post-closet generation are easier in many ways, everyday discrimination still exists in the forms of heterosexism and microaggressions. These forms of discrimination are difficult and risky to talk about, partly because they are often ambiguous, and also because these conversations can disrupt the status quo. In this paper, we explore how the idea of 'discrimination' is more complex than it might first appear, and how the boundaries between 'discrimination' and 'not discrimination' are socially constructed. We conducted qualitative interviews with 15 undergraduate students who self-identified as gay men, and used dialogical analysis to explore their identity work. Participants constructed discrimination/not discrimination in different ways as they shifted between different I− positions: I− as authentic individual, I− as what I am not (not camp and not a victim), and I− as powerful. Our analysis indicates the extent to which 'discrimination' is socially constructed (rather than an objective reality), and suggests means by which practitioners and advocates can support clients in talking about discrimination.